2007
DOI: 10.1080/13569770701562658
|View full text |Cite
|
Sign up to set email alerts
|

Differences in political participation between young and old people

Abstract: People often complain about the supposed laziness and ineptitude of the younger generation, remonstrating their lack of respect for the traditions and seniority of the older population. These reactions are not new, however, as Plato voiced similar concerns about the young people of his time:The children now love luxury; they have bad manners, contempt for authority; they show disrespect for elders and love chatter in place of exercise. Children are now tyrants, not the servants of their households. They no lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
0
29

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 29 publications
7
132
0
29
Order By: Relevance
“…In a sense, the very concept of 'politics' is broadened to include things like the political-ethical-based patterns of consumption at local markets (Micheletti, 2003) and food preferences (Micheletti and Stolle, 2009). If all these types of involvement and interest are taken into account, the overall picture is not as dark as conventional assessments would suggest (Quintelier, 2007). In the United States, if not in Europe, scholars have recently reported on 'an unmistakable expansion of youth interest in politics and public affairs' (Sander and Putnam, 2010: 11).…”
Section: Passivity and Participation Among Young Citizensmentioning
confidence: 90%
“…In a sense, the very concept of 'politics' is broadened to include things like the political-ethical-based patterns of consumption at local markets (Micheletti, 2003) and food preferences (Micheletti and Stolle, 2009). If all these types of involvement and interest are taken into account, the overall picture is not as dark as conventional assessments would suggest (Quintelier, 2007). In the United States, if not in Europe, scholars have recently reported on 'an unmistakable expansion of youth interest in politics and public affairs' (Sander and Putnam, 2010: 11).…”
Section: Passivity and Participation Among Young Citizensmentioning
confidence: 90%
“…Others have found that young people feel unheard by politicians and consequently withdraw from formal political activities, engaging in newer forms of participation, such as signing petitions (e.g. Quintelier, 2007;Sloam, 2014). Evidence has suggested that the young engage in politics as individuals, rather than as part of large organisations (Fieldhouse et al, 2007).…”
Section: Engagement In and With Politicsmentioning
confidence: 99%
“…During the last 10-15 years, researchers have increasingly critiqued the narrow conception of politics in studies of adolescents' interest and participation in political activities (O'Toole, 2003;Marsh et al, 2007;Quintelier, 2007;Manning, 2010;Kallio & H€ akli, 2013). These studies have noted that focusing on formal political activities limits the opportunities to learn about involvement in other civic or political activities or how respondents define political participation (EdComs, 2008).…”
Section: Engagement In and With Politicsmentioning
confidence: 99%
“…Instead, research indicates that this group do take part in differing forms of political action (Quintelier, 2007). Research conducted by Norris (2003) indicates that young people are more likely to engage in 'cause-oriented' styles of politics (or what Pattie et al, [2004] refer to as 'micro-politics') than they are in 'formal' politics -participation that uses less institutionalised methods such as demonstrations, boycotts, and direct action.…”
mentioning
confidence: 99%